Estudo biomecânico do processo de aquisição da marcha independente em bebês - Levada, Giovana (2011)
ABSTRACT The acquisition of independent walking is an important motor milestone and can be considered the greatest biomechanical challenge in infanthood. In the first 5-6 months of independent walking, important transitions appear in all gait parameters. One aspect to take notice is the high level of variability during this acquisition process. Based on these characteristics, this work contributed to better understand the acquisition process of independent walking according to biomechanical variables. A longitudinal study was conducted with three different assessments along a threemonth period. Kinetic and kinematic variables were analyzed. Ten toddlers of 13 months without any neuromuscular disorders participated in this study. The project was approved by the Sao Carlos University Ethics Committee (Number 013/2010). The toddlers were encouraged to walk freely on a 5 meter walkway, keeping natural speed. The Study I verified the variability in the Ground Reaction Forces (GRF) during the assessments. The Friedman s ANOVA did not reveal significant differences in the discrete variables, despite the reduction in the Coefficient of Variation (CV) of the vertical and horizontal components of the GRF. The Study II verified changes in kinematic variables, using spatio-temporal parameters and knee, ankle and hip joint angles. Once again no significant differences were found, however toddlers showed speed and cadence improvements and also reduction in the double support time and stride duration. Moreover, there was an increase in the first wave of the knee flexion. The gait experience acquired during the first threemonths of independent walking to these children was not enough to cause significant changes in the biomechanical variables studied here. However, the progressive reduction in the CV between assessments and the changes in some spatio-temporal parameters suggest progressive gait maturation.